Altered Peroxisome Proliferator-Activated Receptor Alpha Signaling in Variably Diseased Peripheral Arterial Segments - Engel, Connor; Meade, Rodrigo; Harroun, Nikolai; Penrose, Amanda; Shafqat, Mehreen; Jin, Xiaohua; DeSilva, Gayan; Semenkovich, Clay; Zayed, Mohamed (Frontiers in Cardiovascular Medicine, 2022)
Objective Peripheral atherosclerosis that accumulates in the extracranial carotid and lower extremity arteries can lead to significant morbidity and mortality. However, atherosclerotic disease progression is often not homogenous and is accelerated by diabetes. We previously observed increased phospholipid content in minimally (Min)-diseased arterial segments compared to maximally (Max)-diseased segments. Since Peroxisome Proliferator-Activated Receptor alpha (PPARα) is a key regulator of lipid metabolism, we hypothesized that it may have differential expression and signaling in Min vs. Max-diseased peripheral arterial segments. Methods Eighteen patients who underwent carotid endarterectomy (CEA), and 34 patients who underwent major lower extremity amputation were prospectively enrolled into a vascular tissue biobank. Min and Max-diseased segments were obtained in real-time from CEA plaque and amputated lower extremity arterial segments. mRNA and protein were isolated from specimens and the relative expression of ppara, and its downstream genes Acyl-CoA Oxidase 1 (acox1) and Carnitine Palmitoyltransferase 1A (cpt1a) were also evaluated. We evaluated gene expression and protein content relative to atherosclerotic disease severity and clinical diabetes status. Gene expression was also evaluated relative to Hemoglobin A1c and serum lipid profiles. Results In CEA segments of patients with diabetes, we observed significantly higher ppara and acox1 gene expression (p < 0.01 and p < 0.001 respectively), and higher PPARα protein content (p < 0.05). Hemoglobin A1c significantly correlated with expression of ppara (R2 = 0.66, p < 0.001), acox1 (R2 = 0.31, p < 0.05), and cpt1a (R2 = 0.4, p < 0.05). There was no significant difference in gene expression between Min vs. Max-diseased CEA plaque segments. Conversely, in lower extremity arterial segments of patients with diabetes, we observed significantly lower ppara, acox1, and cpt1a expression (p < 0.05, p < 0.001, and p < 0.0001 respectively). Interestingly, CPT1A content was lower in arterial segments of patients with diabetes (p < 0.05). Hemoglobin A1c and HDL-cholesterol had negative correlations with ppara (R2 = 0.44, p < 0.05; R2 = 0.42, p < 0.05; respectively). Conclusion This study demonstrates the significant differential expression of ppara and its immediate downstream genes in human carotid and lower extremity arteries relative to disease severity and diabetes. These findings highlight that mechanisms that influence atheroprogression in the carotid and lower extremities peripheral arteries are not homogenous and can be impacted by patient diabetes status and serum cholesterol profiles. Further elucidating these differential molecular mechanisms can help improve targeted therapy of atherosclerosis in different peripheral arterial beds.